PENGARUH KUALITAS PELAYANAN DAN LOKASI TERHADAP KEPUTUSAN PEMBELIAN DENGAN HARGA SEBAGAI VARIABEL MODERATING - Lesli Purnawati, Ernawati & Retno Susanti (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2017)
The purpose of this research is to know the quality of the service, the location effect significantlyon the buying decision at the Minimarket Andhika Nusukan and find out the prices moderate the effect of service quality and location on buying decision at the MinimarketAndhika Nusukan. This research method using a survey method conducted to the consumer of Minimarket Andhika Nusukan. The type of data that used is qualitative and quantitative data. The source of the data used in this research is the primary data. The method to collect the data is questionnaire. The data were analyzed using Validity, Reliability, and classic Assumption test, multiple linear analysis, t Test, f Test, the coefficient of Determination, and Absolute Difference Test. The results of this research proved the quality of service, location, and price effect significantly to buying decisions at the Minimarket Andhika Nusukan. From the results of the absolute difference test proved that the price moderate the effectof the quality of service and location on buying decision at the Minimarket Andhika Nusukan.Keywords: service quality, location, price, buying decision